Creative Management and Innovation: Building Competitive Advantage in The Contemporary Era - Rokhmad Slamet; Harries Madiistriyatno; Munir Azhari (Return : Study of Management, Economic and Bussines, 2023)
In the world of business and enterprise, competition is something that cannot be avoided. Especially in this contemporary era, business practices are experiencing very rapid changes due to advances in digital technology which requires business people to be ready to face competition. In an effort to face competition in business, an attitude of discipline, creativity and innovation is needed by business people or businesses. In an effort to maintain market share, an entrepreneur must be able to see an opportunity and have the courage to take a risk. It is through courage and opportunity that an entrepreneur becomes equipped to remain capable and even win market competition. This research aims to find out what kind of creativity and innovation are carried out by business actors in dealing with changes in market share in the current era. This research uses a qualitative research method using a case study approach. The results of this research are that the application of creative management and innovation carried out by the UMKM industry, Ms. Sumiatin's peanut brittle business and the restaurant industry, namely Lim's Cafe Kisaran and Bang Kendik Cafe Rantauparat, has had a positive impact and is able to create competitive advantages in the contemporary era.